2022
DOI: 10.1080/1478422x.2022.2137979
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of corrosion inhibitor system through N-heterocyclic compounds: a review

Abstract: Organic compounds containing heteroatoms have been comprehended to exhibit a remarkable tendency towards corrosion mitigation. This corrosion mitigating tendency is enabled by the presence of electron clouds composed of lone pairs, pi-electrons, which allow them to be adsorbed over metallic equivalents. Because of the availability of nitrogen as heteroatoms, these compounds are being extensively used for corrosion diminution. This article looks at a variety of heterocyclic organic compounds like imidazole, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Numerous factors influence the inhibition process, with the metal surface charge and the state of organic molecules in a corrosive environment being particularly influential in the adsorption process. [95][96][97][98][99] Previous research [100][101][102][103] has demonstrated that mild steel surfaces in HCl solution carry a net positive charge, leading to preferential adsorption of chloride ions on the surface. As a result, excess electrons are generated, facilitating the adsorption of cationic species.…”
Section: Inhibition Mechanismmentioning
confidence: 99%
“…Numerous factors influence the inhibition process, with the metal surface charge and the state of organic molecules in a corrosive environment being particularly influential in the adsorption process. [95][96][97][98][99] Previous research [100][101][102][103] has demonstrated that mild steel surfaces in HCl solution carry a net positive charge, leading to preferential adsorption of chloride ions on the surface. As a result, excess electrons are generated, facilitating the adsorption of cationic species.…”
Section: Inhibition Mechanismmentioning
confidence: 99%
“…As part of our investigation, we currently explore the integration of the 7-DAC core to nitrogenated heterocycles, as plausible interfaces between 7-DAC and complexes of transition metal ions. In this context, the 1,2,4-triazole ring caught our attention due to its known effectiveness as part of corrosion inhibitors for lowcarbon steel, [20][21][22][23][24][25][26] and to its use as a building block of lightemitting devices in organic electronic applications due to the luminescent properties and ready thin-lm formation of several of its derivatives. [27][28][29][30][31] Moreover, it has recently become an important synthon for Metal-Organic Frameworks (MOFs) and coordination polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition characteristic of natural extracts is greatly depends on available heteroatoms (O, N and S) with lone pair electrons and larger molecular size. These heteroatoms contain electron-rich sites which act as centre for adsorption, enables the inhibitor to adsorb on metallic surface, and hence, restrict the corrosion reactions [14]- [17].…”
Section: Introductionmentioning
confidence: 99%